EFL teacher educators’ experiences in teaching critical reading: evidence from Indonesia - Muhammad Yunus; M. Faruq Ubaidillah (Journal on English as a Foreign Language, 2021)
While extensive studies have explored issues of teaching critical reading in English as a foreign language (EFL) classes, there is a paucity of research that examines teacher educators’ conceptions of teaching critical reading in the EFL contexts. To fill the gap, this phenomenological study probes into EFL teacher educators’ experiences in teaching critical reading. It specifically looks at teacher educators’ conceptions of teaching critical reading and how their teaching practices contribute to the development of students’ critical reading skills. Data were generated through in-depth interviews with nine teacher educators in a private university in Malang, Indonesia. Findings suggest that the teacher educators’ conceptions of teaching critical reading, as geared by their lived experiences, involve basic conceptions of teaching critical reading, teaching critical reading from a philosophical lens, and critical thinking empowerment in reading classes. The study also documents that teaching critical reading encompasses higher order thinking skills enacted in the process of reading. Practically, the study’s findings call for the enactment of pedagogic trainings for teacher educators in order to construe their basic tenets of teaching critical reading, the philosophies behind such a teaching practice, and the empowered learning activities in the reading classes.